White matter correlates of contextual pavlovian fear extinction and the role of anxiety in healthy humans - Nees, Frauke; Pohlack, Sebastian; Grimm, Oliver; Winkelmann, Tobias; Zidda, Francesca; Flor, Herta (Cortex, 2019)
Pavlovian contextual fear extinction is viewed as an important mechanism for behavioral adaptation in everyday life, including challenging situations of stress and anxiety. It has frequently been shown to relate to the function of brain areas like the hippocampus and medial prefrontal cortex (mPFC), while the role of structural properties, like white matter tracts in these regions, has been less studied. We employed diffusion tensor imaging to determine structural white matter connectivity (cingulum and uncinate fasciculus) correlates of contextual pavlovian fear extinction indicators measured through functional magnetic resonance imaging, skin conductance responses (SCRs) and self-reports of valence, arousal and contingency in 93 healthy individuals. Higher fractional anisotropy values in the hippocampal cingulum were significantly related to higher SCRs during extinction of contextual conditioned responses (explained variance: 11.2%) as an indicator of extinction deficits on the level of physiological arousal. However, FA was neither related to any of the other fear extinction measures, nor did we find associations with functional extinction responses in the hippocampus or mPFC. Trait anxiety was a significant moderator of the SCR-hippocampal cingulum association (explained variance: 32.09%). The data add evidence for a critical role of the hippocampal formation in contextual pavlovian extinction, and, together with the strong effect of trait anxiety, may have implications for the development of anxiety disorders where contextual extinction learning deficits are observed.